Al-'Arābīyah and Basa Sunda: Ideologies of Translation and Interpretation among the Muslim of West Java - Benjamin G. Zimmer (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This article reflects on these questions as they relate to the Sundanese-speaking population of western Java, Indonesia's second largest ethnic group.